**(iii) x**

^{2}+ 5x – 14 = 0, x = √2 , –7, 3**Sol.**

**a) By putting x = √2 in L.H.S. we get**

**L.H.S. = ( √2 )**

^{2}+ 5( √2 ) – 14**= 2 + 5√ 2 – 14**

**= 5 √2 – 12**

**≠ R.H.S.**

**∴**

**L.H.S. ≠ R.H.S.**

**Thus equation is not satisfied.**

**So, √2 is not the root of the given quadratic equation.**

**b) By putting x = –7 in L.H.S. we get**

**L.H.S. = (–7)**

^{2}+ 5(–7) – 14**= 49 – 35 – 14**

**= 49 – 49**

**= 0**

**= R.H.S.**

**∴**

**L.H.S. = R.H.S.**

**Thus equation is satisfied.**

**So, –7 is the root of the given quadratic equation.**

**c) By putting x = 3 in L.H.S. we get**

**L.H.S. = (3)**

^{2}+ 5(3) – 14**= 9 + 15 – 14**

**= 24 – 14**

**= 10**

**≠ R.H.S.**

**∴**

**L.H.S. ≠ R.H.S.**

**Thus equation is not satisfied.**

**So, 3 is not the root of the given quadratic equation.**